Addressing the Asian Diaspora: A Review of Four Different Books on the Subject - G. Davis, Rocío (Miscelánea: A Journal of English and American Studies, 2002)
Review of: Encounters: People of Asian Descent in the Americas, by Roshni Rustomji-Kerns, Rajini Srikanth, and Leny Mendoza Strobel (eds.). Lanham: Rowman & Littlefield, 1999. Identidad étnica y género en la narrativa de escritoras chinoamericanas, by Begoña Simal González. La Coruña: Servicio de Publicaciones de la Universidad de La Coruña, 2000. Negotiating Identities: An Introduction to Asian American Women’s Writing, by Helena Grice. Manchester: Manchester UP, 2002. The Chutneyfication of History: Salman Rushdie, Michael Ondaatje, Bharati Mukherjee and the Postcolonial Debate, by Mita Benerjee. Heidelberg: Universitätverlag C. Winter, 2002.